دور تنبؤ بالمبيعات على مردودية المؤسسة الإقتصادية بالجزائر - بكوش, وهيبة (My University, 2019)
Our study aimed to different methods of sales forecasting to clarify and compromises between them and choose appropriate method which gives values for sales of high quality. It is in order to achieve the desired objective of the study, and dividing our work into three chapters, where he treated the first chapter theoretical foundations of forecasting in general and in particular sales forecasting. The second chapter, we talked to was the amount of methods and quality of sales forecasting, and how to evaluate and choose a method to predict. The third chapter, and it was then the case of some quantitative methods and then choose the method that provides the highest quality to predict the sales organization. And we tried as much as possible during the study of the application to take advantage of available information. And we can say that the study of subject is just an attempt to put a scientific methodology to streamline Almarssh uses, and can be regarded as a fundamental axis of the sales forecast in the company's size.
مؤسسة سيراميس مستغانم
Keywords: التنبؤ بالمبيعات ، مؤسسة إقتصادية ،مؤسسة سيراميس مستغانم